One-year prevalence and clinical characteristics in chronic dizziness: The 2019–2020 Korean National Health and Nutrition Examination Survey - Kim, Eun Ji; Song, Hee-Jung; Lee, Hak In; Kwon, Eunjin; Jeong, Seong-Hae (Frontiers in Neurology, 2022)
Introduction In this cross-sectional study, we investigated the 1-year prevalence and related factors in the general population with an experience of chronic dizziness. Methods This study analyzed persons (n = 5,163) who respond to dizziness and nutrition questionnaire from participant of Korean National Health and Nutrition Examination Survey (KNHANES, 2019-2020). Results Of individuals over 40 years, 25.3% of the general population (61.6% females) reported either dizziness or imbalance for the past year. Moreover, 4.8% of the patients reported they suffered from chronic dizziness or imbalance for more than 3 months. In multiple regression analysis, patients with chronic dizziness were older, females, had lower body mass index (BMI), had stress awareness, and had a history of tinnitus within 1 year (>5 min per episode). Relative to normal body weight, both overweight and mild obesity (obesity stages 1 and 2) were associated with a significantly lower risk of chronic dizziness. Overweight, obesity stage 1, and obesity stage 2 had odds ratios of 0.549 [95% confidence interval (CI), 0.332–0.910], 0.445 (95% CI, 0.273–0.727), and 0.234 (95% CI, 0.070–0.779), respectively. Conclusions In this study, the prevalence of chronic dizziness in the general population was 4.8%. Our study demonstrated that overweight and mild obesity were independently associated with a lower risk of chronic dizziness in adults for the past year. Therefore, the optimal BMI for patients with dizziness should be defined and managed according to an integrated care pathway.